Peran Pendidikan Agama Kristen dalam Membentuk Sikap Inklusif di Tengah Keberagaman - Yesica Hutahaean; Roman Ryanto Lumbantobing; Anju Mayda Serasi Sihombing; Tasya Octavia Situmeang (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This article discusses the role of Christian Religious Education (PAK) in shaping inclusive attitudes of students in the midst of diverse Indonesian society. Using a descriptive qualitative approach, this study examines how PAK can teach the values ​​of love, justice, and respect for differences, and their impact on students' character. The results of the study indicate that PAK not only functions as a transmitter of the doctrine of faith, but also as a means to promote tolerance and interfaith dialogue. Teachers play an important role as facilitators who create a safe and supportive learning environment, and integrate multicultural values ​​into the curriculum. Although PAK faces challenges in the learning approach, collaboration between the church, school, and family can strengthen the impact of religious education. Thus, PAK has great potential in shaping a tolerant generation committed to social justice in a pluralistic society.